2021
DOI: 10.1021/acs.langmuir.1c02088
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering of Graphene to Modulate pH Response of Graphene Devices

Abstract: Graphene-based pH sensors are a robust, durable, sensitive, and scalable approach for the sensitive detection of pH in various environments. However, the mechanisms through which graphene responds to pH variations are not well-understood yet. This study provides a new look into the surface science of graphene-based pH sensors to address the existing gaps and inconsistencies among the literature concerning sensing response, the role of defects, and surface/solution interactions. Herein, we demonstrate the depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 77 publications
3
28
0
Order By: Relevance
“…cations 57,68,69 or pH. 61 In addition, we have demonstrated the use of two different sensor geometries, which expands the possibilities of sensor deployment. The manual lab-based device fabrication method employed in this study does not lend itself to achieving narrow tolerances, resulting in variations in the magnitude of response between devices.…”
Section: Discussionmentioning
confidence: 91%
“…cations 57,68,69 or pH. 61 In addition, we have demonstrated the use of two different sensor geometries, which expands the possibilities of sensor deployment. The manual lab-based device fabrication method employed in this study does not lend itself to achieving narrow tolerances, resulting in variations in the magnitude of response between devices.…”
Section: Discussionmentioning
confidence: 91%
“…Since the holes are the majority carrier in graphene due to the presence of electron-withdrawing oxygen atoms, n-doping the surface reduces the charge carriers in the chemiresistor and makes it more resistive. In contrast, electrostatic p-doping of OH − aq ions accumulated in the Stern layer increases the current at a high pH [ 26 ]. The schematic illustrations of the formation of the electrochemical double layer (EDL) in acidic solutions are shown in Figure 2 d. It should be noted that the charge transfers through the formation of the EDL by H 3 O + and OH − are considered fully nonfaradaic.…”
Section: Resultsmentioning
confidence: 99%
“…This means that decreasing the pH reduces the current, while increasing the pH toward the basic solution increases n-doping. We have recently shown that the defect-induced pH response of graphene originates from the protonation/deprotonation of carboxyl and amine at a low pH and hydroxyl groups at a high pH [ 26 ]. For example, in carboxyl groups, upon decreasing the pH to 3 (below the pK a = 3.1), the is protonated to -COOH, and the surface becomes p-doped.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations